Productive Zakat Law Implementation in Mentor Empowerment for Entrepreneurial Character Building and Mustahiq Empowerment - Husnul Khatimah; Nuradi Nuradi; Jaih Mubarok (Indonesian Journal of Islamic Economics and Finance)
This study examines the law of productive zakat and its implementation in the mentor empowerment program for the formation of entrepreneurial character and empowerment of mustahiq. This study uses a library method with a qualitative approach and descriptive analysis that examines various opinions and sources of law on productive zakat. The study's results indicate differences of opinion among scholars regarding the permissibility of productive zakat. One group argues it is forbidden based on the premise of direct distribution and ownership of zakat funds by mustahiq. Another group allows productive zakat because of its greater benefits and impacts. The third view, namely moderate, allows productive zakat after the urgent needs of mustahiq are met. This study is more inclined towards this third view because it is considered the most appropriate to the current era and needs. The implementation of productive zakat is analyzed through the instruments of mudharabah, murabahah, and qardhul hasan. Mentoring is considered beneficial for business growth and mustahiq welfare. This study provides insight for zakat institutions to improve empowerment strategies and strengthen productive zakat policies.